2008
DOI: 10.1073/pnas.0806291105
|View full text |Cite
|
Sign up to set email alerts
|

STAT92E is a positive regulator ofDrosophilainhibitor of apoptosis 1 (DIAP/1) and protects against radiation-induced apoptosis

Abstract: The proapoptotic factors Reaper, Hid, Grim, and Sickle regulate apoptosis in Drosophila by inhibiting the antiapoptotic factor DIAP1 (Drosophila inhibitor of apoptosis 1). Heat, UV light, x-rays, and developmental signals can all increase the proapoptotic factors, but the control of transcription of the diap1 gene is unclear. We show that in imaginal discs the single Drosophila STAT protein (STAT92E) when activated can directly increase DIAP1 through binding to STAT DNA-binding sites in the diap1 promoter. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
2
55
0
Order By: Relevance
“…In the Drosophila developing wing, phosphorylated Stat92E has been shown to be necessary for protection against stress-induced apoptosis, but not for wing developmental apoptosis (Betz et al, 2008). Here we provide evidence that Upd and the JAK/STAT pathway control developmental apoptosis during Drosophila oogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…In the Drosophila developing wing, phosphorylated Stat92E has been shown to be necessary for protection against stress-induced apoptosis, but not for wing developmental apoptosis (Betz et al, 2008). Here we provide evidence that Upd and the JAK/STAT pathway control developmental apoptosis during Drosophila oogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…So far, only isolated studies have implicated JAK/STAT in cell survival (Betz et al, 2008;Hasan et al, 2015;Guarner et al, 2014;Ohayon et al, 2009). For example, the apoptosis inhibitor IAP has been suggested to be a positively regulated target of Stat92E, protecting cells from apoptosis (Betz et al, 2008;Hasan et al, 2015). We identify the JAK/STAT effector Zfh2 as a potential repressor of kay and hid activity -a molecular pathway expected to restrain excessive JNK-activity and induction of apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, continuous overexpression of Upd can also induce apoptosis (not shown) and, thus potentially also sustained JNK-dependent compensatory proliferation, driving tissue growth. So far, only isolated studies have implicated JAK/STAT in cell survival (Betz et al, 2008;Hasan et al, 2015;Guarner et al, 2014;Ohayon et al, 2009). For example, the apoptosis inhibitor IAP has been suggested to be a positively regulated target of Stat92E, protecting cells from apoptosis (Betz et al, 2008;Hasan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simplicity makes the Drosophila JAK/STAT pathway an ideal target for loss-offunction studies. Such studies have shown that Drosophila JAK/ STAT signaling is involved in diverse biological processes, including early and late development, innate immunity, germ-cell adhesion, and inhibition of apoptosis (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%